Anisotropic magnetoresistive and magnetic properties of La₀.₅Sr₀.₅CoO₃₋δ film - Belevtsev, B.I.; Krasovitsky, V.B.; Panfilov, A.S.; Chukanova, I.N. (Физика низких температур, 2003)
The magnetic and transport properties of a La₀.₅Sr₀.₅CoO₃₋δ film grown on a LaAlO₃ substrate by pulsed-laser deposition are studied. The properties are found to be influenced by the magnetic anisotropy and inhomogeneity. Magnetoresistance anisotropy is determined by the shape anisotropy of the magnetization and the strain-induced magnetic anisotropy due to the film-substrate lattice interaction. Indications of the temperature-driven spin reorientation transition from an out-of plane orderded state at low temperatures to an in-plane ordered state at high temperatures as a result of competition between the mentioned sources of magnetic anisotropy are found.